ANALISIS FAKTOR-FAKTOR YANG MEMPENGRUHI TINGKAT KURS - Istiono, * (DiE: Jurnal Ilmu Ekonomi dan Manajemen, 2009)
The goal of this research is to know the impact of inflation rate, interest rate, outstanding money to exchange rate. The period of observations are divided into two, year of 1990 – 1996 and year of 2000 – 2006. By using regression analysis are found that for the period of 1990 – 1996, all independent variabels simultaneously affect the exchange rate significantly, but partially only the outstanding money affect significantly to the exchange rate. While for the period of 2000 – 2006, all of the independent variables do not affect the echange rate significantly. Keywords: inflation rate, interest rate, outstanding money, and exchange rate.